Soil osmotic potential and its effect on vapor flow from a pervaporative irrigation membrane - Todman,LC; Chhang,A; Riordan,HJ; Brooks,D; Butler,AP; Templeton,MR (Journal of Environmental Engineering, 2018)
Pervaporative irrigation is a membrane technology that can be used for desalination and subsurface irrigation simultaneously. To irrigate, the tube-shaped polymer membrane is buried in soil and filled with water. Because of the membrane transport process, water enters the soil in the vapor phase, drawn across the membrane when the relative humidity in the air-filled pores is low. Soils are typically humid environments; however, the presence of hygroscopic compounds such as fertilizers decreases the humidity. For example, at 20°C the humidity in air in equilibrium above a saturated ammonium nitrate solution is 63%. Here, experiments showed that the presence of fertilizers in sand increased the water flux across the membrane by an order of magnitude. An expression for vapor sorption into sand containing different hygroscopic compounds was developed and combined with a model of vapor and liquid flow in soil. The success of the model in simulating experimental results suggests that the proposed mechanism, adsorption of moisture from the vapor phase by hygroscopic compounds, explains the observed increase in the flux from the irrigation system.